Analisis Strategi Pemberdayaan Ekonomi Dengan Pendekatan USG Dan SWOT - Yurianto Yurianto (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
The mosque in the history of Islamic civilization is a means to do da'wah and the development of Muslim economic resources. The purpose of this study is to identify the economic potential of the Nurul Iman Mosque, then to analyze the economic potential of the Nurul Iman Mosque in the economy, and to develop strategies in developing the mosque's economy. This study was conducted in a descriptive qualitative approach. The location of Nurul Iman Mosque is very strategic for business activities for the people. The most dominant factor in the economic development of a mosque is a factor in the large number of worshipers. With the cartesius diagram, it is concluded that the grand strategy in the framework of economic development of the Nurul Iman Mosque is the Strength and Opportunity (Strategy S-O) strategy.